FIMD based model validation approaches for Rheumatoid arthritis and associated cardiovascular complications: an attempt towards translational competence - Trupti Dubey; Kirti V. Patel (Belgorod National Research University, 2024)
Introduction: The present in-vivo experiment was designed to validate newly developed rat models for Rheumatoid Arthritis (RA) as well as cardiovascular complications in RA for translational competence of disease with clinical situation. The FIMD (Framework to Identify Models for Disease) method based on etiology, pathophysiology, symptomatology, and response to therapeutic interventions was used to compare these models sensitized with primary (CFA, bovine collagen type II) and secondary inducing agents (high fat diet, lipopolysaccharide) in different combinations. Materials and Methods: Twenty-four Wistar male rats (four groups/n=6) were taken after prevalidation, where a large dataset was analyzed by using statistical methods (one way ANOVA, repeated Measure ANOVA). Among these groups, two best models from RA representative groups and two best models from cardiovascular complications in RA generated groups were taken for final comparison and validation by the same weight score method for obtaining a percentage similarity and validity score using a radar plot based on FIMD to get the best suited model. Results and Discussion: The findings of this study on the basis of FIMD showed that the collagen (0.1 mL)+lipopolysaccharide (10 µg/mL) induced model is closely fit for preclinical events of RA, with the highest validity score (82%) among all groups and the collagen (0.1 mL)+ lipopolysaccharide (10 µg/mL)+HFD represents a validated model (95%) for co-morbid cardiovascular complications in RA. Conclusion: The developed and validated models were a fresh attempt using different inducers sequentially to culminate the emerging issue of extra organ manifestation in existing RA via a similar pathway, which can be a contributor to future research in drug discoveries in pharmacology.